Åfficacy of nutraceutical drug in the intermediate and wet forms of age-related macular degeneration - E. N. Eskina; A. V. Belogurova; A. A. Gvetadze; A. S. Smorchkova (Российский офтальмологический журнал)
The effectiveness of nutraceutical drug containing oxycarotenoids, vitamins and trace elements, aimed at inhibiting the progression of the dry form of age-related macular degeneration (AMD) has been demonstrated in clinical studies.The purpose of this research is to evaluate the effectiveness of long-term use of a nutraceutical drug in reducing the risk of intermediate AMD evolving into wet AMD, and assess whether it is worth using in patients with wet AMD to reduce the average yearly number of intravitreal injections of angiogenesis inhibitors.Materials and methods. In the first part of the study, we monitored 46 patients with intermediate AMD threatening the progression of the disease (those with multiple confluent drusen, drusenoid, pigment epithelium detachment) for a year: some of them received the drug while others had no nutraceutical support. We assessed standard visual functions, as well as reading parameters (on the Salzburg Reading Desk device), spatial frequency contrast sensitivity (SFC) according to the Zebra program, and macular pigment optical density (on the MPOD device). Retina parameters were controlled by photofixation using Kowa and Clarus 500 fundus camera, and by optical coherence tomography with angiography using a Cirrus 5000 Angioplex, Carl Zeiss. The disease was considered to be progressing if signs of neovascular AMD were detected. In the second part of the study, 35 patients with newly diagnosed neovascular AMD were followed up for a year and treated with angiogenesis inhibitors according to the following pattern: three loading injections of aflibercept and then pro re nata. Of two groups of patients with signs of neovascular AMD, one group took a nutraceutical drug (Lutrin, S.C. Rompharm Company S.R.L., Romania). The number of intravitreal injections of aflibercept administered according to indications during the year was estimated.Results. In the first part of the study, patients with intermediate AMD taking the drug showed an increase in MPOD from 0.36 ± 0.11 to 0.45 ± 0.15 (p = 0.05) and a stable state of the retina and visual functions throughout the entire observation period. In 2 patients (12.5 %) who did not take the drug, the disease progressed to a neovascular form. In the second part of the study, the patients taking the drug received an average of 3.4 ± 0.7 intravitreal injections of aflibercept during the year, compared with 5.3 ± 1.2 injections in the control group without nutraceutical support.Conclusion. Nutraceutical drugs are effective in reducing the risk of intermediate AMD evolving into wet AMD, and thus advisable for patients with wet AMD to reduce the average yearly number of intravitreal injections of angiogenesis inhibitors.